Impact of Extrinsic and Intrinsic Motivation Element to People Knowledge Sharing Behavior at Virtual Communities of Practices in Indonesia - Setiawan Assegaff; Kurniabudi Kurniabudi; Erick Fernando (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
One of critical challenge in knowledge management success is to motivate people share their knowledge to others. Prior’s research reveals that motivation as primary driver for people to perform knowledge sharing. Previous study also indicated people influenced by internal (intrinsic) and external (extrinsic) motivation when perform the knowledge sharing. The aim of this article is to investigate and explores how the elements of extrinsic and intrinsic motivation contribute to people intention in perform knowledge sharing in virtual communities. Moreover this study would confirm and understand how this knowledge sharing behavior occurs in Indonesia Context. Many literatures argue that different culture context would produce different of people belief and behavior. This study conducts a survey in a formal virtual community of practices members in one Indonesia Company. Two hundred and four respondents participated in this study. Data was analysis using SEM with Smart PLS Software. This study found that both of those motivations (intrinsic and extrinsic) are positively influences behavior of people knowledge sharing in formal Virtual Communities of Practices. In advance this studies indicate that extrinsic motivation is major motivation element that influencing people in perform knowledge sharing.